2005
DOI: 10.1002/ajh.20301
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal B‐cell lymphoma with sclerosis: Report of 11 cases treated with intensified‐CHOP plus radiotherapy

Abstract: Primary mediastinal B-cell lymphoma (PMBCL) is a clinicopathological entity with aggressive behavior. Retrospective evaluation suggests the need for intensive chemotherapy programs. From 1997 to February 2003, a total of 11 cases of previously untreated PMBCL with sclerosis were treated at our institution with 5 courses of intensified CHOP (ICHOP) regimen and mediastinal irradiation. Three patients were submitted to high-dose chemotherapy with peripheral-blood stem-cell support, followed by radiotherapy, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Other investigators have reported results that compare favorably with those of CHOP, using various intensive regimens [8,11,12]. However, the use of any particular approach is not supported by randomized trials.…”
mentioning
confidence: 82%
“…Other investigators have reported results that compare favorably with those of CHOP, using various intensive regimens [8,11,12]. However, the use of any particular approach is not supported by randomized trials.…”
mentioning
confidence: 82%
“…In a multi‐center study of 138 patients, Todeschini et al 21 used IFRT in initial treatment and showed that this approach significantly improved outcome regardless of the type of chemotherapy (5‐year EFS approximately 92% with IFRT, 78% without IFRT). Similarly, several multinational, retrospective reviews showed that among patients who achieved a PR after induction chemotherapy, RT was able to produce a CR in the majority 23, 24, 33.In Mazzarotto's study 42% of patients were in CR after the chemotherapy and 95% after the addition of IFRT, at a mean dose of 36Gy in 22 fractions. The 5‐year DFS and OS were 93% and 87% respectively 24.…”
Section: Introductionmentioning
confidence: 92%